Reframing in the Translation of News on Israel-Hamas War Published in Kompas Newspaper: Pembingkaian Ulang dalam Penerjemahan Berita Perang Israel-Hamas di Koran Kompas - Muttaqin, Nurul (Jurnal Penerjemahan, 2025)
News outlets might see the same event from different points of view. Such different perspectives can also be observed in translated news and its sources. This study discusses the reframing in the translation of news on the Israel-Hamas war in Kompas in the Indonesian language, translated from the English news agency Associated Press (AP). This research aims to examine how reframing was applied by Kompas when translating news texts from AP. It adopts a qualitative approach and is product-oriented research as it uses translated text as the primary analysis focus and to draw conclusions. The study draws on reframing and appraisal theory. Kompas and AP were chosen as data sources for their reputable sources of news and significant impact on their respective scopes. Data analysis yielded different categories of results. The first is units of analysis (n=123), which fall into two categories: nonappraisal (n=72) and appraisal (n=51). The second is the assessment shifts of the evaluative resources that can be classified into three categories: Israel and Hamas as entities, actions taken by Israel and Hamas, and supporters of Israel and Hamas. The third is that Kompas tends to amplify assessments of Israel from negative to more negative points of view, while presenting Hamas in a more positive frame, particularly related to the translation of the group's names. The results of this study support the view that Kompas attempts to meet the Indonesian target readers' expectations and take the government’s partial stance towards Palestine.